Intron 17 of the human retinoblastoma susceptibility gene encodes an actively transcribed G protein-coupled receptor gene. - Herzog, H; Darby, K; Hort, Y J; Shine, J (Genome Research, 1996)
The human retinoblastoma susceptibility gene, a member of the tumor suppressor gene family, is located on chromosome 13q14.12-13q14.2 and consists of 27 exons that are distributed over 180 kb. This study shows that intron 17, the largest in size, consisting of nearly 72,000 bp, contains an open reading frame encoding a novel G protein-coupled receptor in the reverse orientation relative to the transcription of the retino-blastoma susceptibility gene. Correction of a frameshift mutation revealed that this novel G protein-coupled receptor is the human homolog of a chicken T-cell-specific receptor cDNA. This is an additional description of an actively transcribed protein-encoding gene positioned within an intron of another gene, suggesting that introns can have important structural functions.